Olfactory function changes and the predictive performance of the Chinese Smell Identification Test in patients with mild cognitive impairment and Alzheimer's disease - Mi, Yan; Ma, Xiaojuan; Du, Shan; Du, Chengxue; Li, Xiaobo; Tan, Huihui; Zhang, Jie; Zhang, Qi; Shi, Wenzhen; Zhang, Gejuan; Tian, Ye (Frontiers in Aging Neuroscience, 2023)
Objectives: Olfactory disorder is one of the sensory features that reflects a decline in cognitive function. However, the olfactory changes and discernibility of smell testing in the aging population have yet to be fully elucidated. We aimed to evaluate changes in the olfactory identification abilities of patients with MCI and AD using the Chinese smell identification test (CSIT) and the performance of the CSIT in distinguishing cognitive decline from normal aging individuals. Methods: Eligible participants aged over 50 years were enrolled in this cross-sectional study between October 2019 and December 2021, and they were divided into MCI, AD and cognitively normal control (NC). All subjects were assessed by neuropsychiatric scales, the activity of daily living scale and the 16-odor CSIT test; we also recorded test performance and the severity of olfactory impairment. Results: In total, 366 eligible participants were recruited, including 188 subjects with MCI, 42 patients with AD and 136 NCs. Patients with MCI achieved a mean CSIT score of 13.06±2.05 while patients with AD achieved a mean score 11.38±3.25; these scores were significantly lower than those of the NC group (14.6±1.57) (P<0.001). Analysis showed that 19.9% of NCs exhibited mild olfactory impairment while 52.7% of MCI and 69% of AD patients suffered from mild to severe olfactory impairment. CSIT score was positively correlated with MoCA and MMSE scores. CIST score and the severity of olfactory impairment were identified as robust indicators for MCI and AD, even after adjusting for age, gender, and level of education. As two important confounders influencing cognitive function, age and educational level did not exhibit significant interactive effects with CIST in determining the risk of MCI or AD. The area under curve (AUC) generated from ROC curves were 0.738 and 0.813 in distinguishing MCI and AD patients from NCs by CSIT score with an optimal cut-off of 13 and 11, respectively. The AUC for CSIT in distinguishing AD from MCI was 0.62. Conclusions: The olfactory identification function is frequently affected in MCI and AD. CSIT is a beneficial tool for early screening of cognitive impairment among elderly patients with cognitive or memory complaints.